2017
DOI: 10.1007/s00394-017-1581-1
|View full text |Cite
|
Sign up to set email alerts
|

Whole milk consumption and risk of cardiovascular disease and mortality: Isfahan Cohort Study

Abstract: Less than daily intake of whole milk was associated with a statistically significant, although modest, lower risk of CVD compared with non-consumption, but this potential benefit may not extend to daily intake in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…In general, a lower risk or no association is reported for total dairy intake, non-fermented milk, fermented milk and cheese and the studied cardiometabolic outcomes. Only single studies indicate a greater risk with any of the cardiometabolic outcomes [9]. The results in the present study conform to the majority of studies in that both non-fermented milk and cheese were associated with lower HR in the basic models, but adjustment for multiple potential lifestyle confounders attenuated the effect.…”
Section: Discussionsupporting
confidence: 86%
“…In general, a lower risk or no association is reported for total dairy intake, non-fermented milk, fermented milk and cheese and the studied cardiometabolic outcomes. Only single studies indicate a greater risk with any of the cardiometabolic outcomes [9]. The results in the present study conform to the majority of studies in that both non-fermented milk and cheese were associated with lower HR in the basic models, but adjustment for multiple potential lifestyle confounders attenuated the effect.…”
Section: Discussionsupporting
confidence: 86%
“…From the Malmö Diet and Cancer cohort 16 , the results on total dairy and butter were included in the data synthesis, and from the EPIC-NL cohort 52 , the results on total dairy, low-fat dairy and high-fat dairy were included in the data synthesis due to the different exposures than in the EPIC cohort 21 . Thus, 30 studies were included in the qualitative data synthesis [12][13][14][15][16][17][18][19][20][21][22][23][36][37][38][39][40][41][42][43][44][45]47,48,[50][51][52][53]55,56 (20 studies for CHD 12,13,[16][17][18][19][20][21][22][37][38][39][40]45,48,[50]<...>…”
Section: Resultsmentioning
confidence: 99%
“…No studies on peripheral artery disease were identified. Table 1 shows the characteristics of the 20 studies on CHD 12,13,[16][17][18][19][20][21][22][37][38][39][40]45,48,[50][51][52][53]56 . Among the 20 studies, 5 presented gender-specific results 17,20,21,50,53 , 3 comprised only men 13,45,56 and 3 comprised only women 12,18,40 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a 2017 study by Tognon et al, all-cause mortality is significantly higher among adults who consumed full-fat milk compared to medium- or low-fat milk [15]. Similarly, Talaei et al found that Iranians who drink whole milk daily are at higher risk of all-cause mortality than their counterparts [16]. Likewise, whole milk intake is predictive of elevated prostate cancer mortality in studies by Lu et al [17] and Song et al [18].…”
Section: Introductionmentioning
confidence: 99%